The Effectiveness of the Buzzy Device for Pain Relief in Children During Intravenous Injection: Quasirandomized Study - Yen-Hua Cho; Yi-Chien Chiang; Tsung-Lan Chu; Chi-Wen Chang; Chun-Chu Chang; Hsiu-Min Tsai (JMIR Publications, 2022)
BackgroundIntravenous injection is the most common medical treatment and the main cause of pain in hospitalized children. If there is no appropriate health care for pain relief, the proportion of moderate and severe pain often exceeds 70%. With nonpharmaceutical-based pain management, Buzzy is recognized as an effective device for rapidly relieving injection pain in hospitalized children. However, Buzzy is not widely used in Asia and very few experimental studies in Asia have addressed the effectiveness of the Buzzy device at treating needle pain in hospitalized children. ObjectiveThe main purpose of this study was to investigate the effectiveness of the Buzzy device for diminishing pain levels among hospitalized children in Taiwan. MethodsWe applied a quasiexperimental design with random assignment. According to the time of admission, child participants were randomly assigned to treatment and nontreatment groups. The Buzzy device was applied as an intervention in this study. The samples size was 30 per group. The study participants were recruited from the pediatric ward of a medical center in northern Taiwan. The research data were collected longitudinally at three time points: before, during, and after intravenous injection. Three instruments were used for assessment: a demographic information sheet, the Wong-Baker Face Scale (WBFS), and the Faces Legs Activity Cry Consolability (FLACC) scale. The data were analyzed by descriptive analysis, the Mann-Whitney U test, the Wilcoxon signed-rank test, and the χ2 test. ResultsA total of 60 hospitalized children aged 3 to 7 years participated in this study, including 30 participants in the treatment group and 30 participants in the nontreatment group. The average age of children in the treatment and nontreatment groups was 5.04 years and 4.38 years, respectively. Buzzy significantly mitigated pain in children during intravenous injection with a significant difference between the two groups in pain-related response (FLACC) and actual pain (WBFS) (Z=-3.551, P<.001 and Z=-3.880, P<.001, respectively). The children in the treatment group had a significantly more pleasant experience than those in the nontreatment group (Z=-2.387, P=.02). When Buzzy was employed, the children experienced less pain than they did during previous intravenous injections (Z=-3.643, P<.001). ConclusionsThe intervention of using the Buzzy device was effective in reducing pain levels of intravenous injection among hospitalized children. The specific focus on children in Asia makes a valuable contribution to the literature. For clinical application, the reliable pain relief measure of Buzzy can be used in other Asian children to help health care providers improve noninvasive care among children. For future applications, researchers could integrate Buzzy into therapy-related games and a technology-based app to increase the efficiency of use and provide more data collection functions.